Relationship Between the Goldberg Spectrum and the B-Fredholm Spectra - Benharrat, Mohammed; Messirdi, Bekkai (Sarajevo Journal of Mathematics, 2017)
A classical result of J. Ph. Labrousse (Rev. Roumaine Math. Pures Appl. 25, 1391-1394, 1980) concerning the symmetric difference between the essential quasi-Fredholm spectrum and the Goldberg spectrum of closed operators in Hilbert spaces is extended to the case of B-Fredholm spectra. The obtained results are used to describe the essential spectrum and some B-Fredholm spectra of some transport operators.